Identification and sequence analysis of putative tocopherol biosynthesis HPPD and VTE3 genes in Typhonium flagelliforme mutants - Nesti Fronika Sianipar; Sitti Dhiffah Nabilah Abdul; Khoirunnisa Assidqi; Reflinur Reflinur; Dwiyantari Widyaningrum; Endang Rahmat; Youngmin Kang (Genetic Resources and Crop Evolution, 2026)

Mitochondrial genome characterization and comparative study in shallots (Allium cepa L. var. aggregatum) - Zeeshan Ali; Tri Joko Santoso; Reflinur; Tri Handayani; Alberta Dinar Ambarwati; Atmitri Sisharmini; Aniversari Apriana; Suci Rahayu; Dwinita Wikan Utami (Plant Gene, 2026)

Development of CRISPR/Cas9 construct for targeted mutagenesis of callose synthase 7 gene in Indonesia's Mandarin citrus genotypes toward managing huanglongbing disease - Kristianto Nugroho; Mia Kosmiatin; Tri Joko Santoso; Agus Purwito; Dewi Sukma; Ali Husni; Chaireni Martasari; Alina Akhdiya; Hadi Mohammad Yusuf; Atmitri Sisharmini; Aniversari Apriana; Reflinur Reflinur (Physiological and Molecular Plant Pathology, 2026)

Morphological and molecular assessment of Indonesia’s shallot (Allium cepa L. var. aggregatum) genotypes based on microsatellite and start codon targeted markers - Tri Joko Santoso; Kristianto Nugroho; Tri Handayani; Alberta Dinar Ambarwati; Chotimatul Azmi; Rini Murtiningsih; Atmitri Sisharmini; Aniversari Apriana; Zeeshan Ali; Dwinita Wikan Utami; Reflinur Reflinur (Genetic Resources and Crop Evolution, 2026)

Genetic diversity and population structure of Indonesia’s mandarin citrus genotypes using simple sequence repeat and start codon targeted markers - Kristianto Nugroho; Tri Joko Santoso; Mia Kosmiatin; Dewi Sukma; Agus Purwito; Ali Husni; Reflinur Reflinur; Puji Lestari (Genetic Resources and Crop Evolution, 2025)

OsCOP1 regulates embryo development and flavonoid biosynthesis in rice (Oryza sativa L.) - Backki Kim; Rihua Piao; Gileung Lee; Eunbyeol Koh; Yunjoo Lee; Sunmin Woo; Reflinur; Wenzhu Jiang; Endang M. Septiningsih; Michael J. Thomson; Hee-Jong Koh (Theoretical and Applied Genetics, 2021)
Key message Novel mutations of OsCOP1 were identified to be responsible for yellowish pericarp and embryo lethal phenotype, which revealed that OsCOP1 plays a crucial role in flavonoid biosynthesis and embryogenesis in rice seed. Abstract Successful production of viable seeds is a major component of plant life cycles, and seed development is a complex, highly regulated process that affects characteristics such as seed viability and color. In this study, three yellowish-pericarp embryo lethal ( yel ) mutants, yel - hc , yel - sk , and yel - cc , were produced from three different japonica cultivars of rice ( Oryza sativa L). Mutant seeds had yellowish pericarps and exhibited embryonic lethality, with significantly reduced grain size and weight. Morphological aberrations were apparent by 5 days after pollination, with abnormal embryo development and increased flavonoid accumulation observed in the yel mutants. Genetic analysis and mapping revealed that the phenotype of the three yel mutants was controlled by a single recessive gene, LOC _ Os02g53140 , an ortholog of Arabidopsis thaliana CONSTITUTIVE PHOTOMORPHOGENIC 1 ( COP1 ). The yel - hc , yel - sk , and yel - cc mutants carried mutations in the RING finger, coiled-coil, and WD40 repeat domains, respectively, of OsCOP1 . CRISPR/Cas9-targeted mutagenesis was used to knock out OsCOP1 by targeting its functional domains, and transgenic seed displayed the yel mutant phenotype. Overexpression of OsCOP1 in a homozygous yel-hc mutant background restored pericarp color, and the aberrant flavonoid accumulation observed in yel-hc mutant was significantly reduced in the embryo and endosperm. These results demonstrate that OsCOP1 is associated with embryo development and flavonoid biosynthesis in rice grains. This study will facilitate a better understanding of the functional roles of OsCOP1 involved in early embryogenesis and flavonoid biosynthesis in rice seeds.

Characterization and mapping of d13, a dwarfing mutant gene, in rice - Md. Babul Akter; Rihua Piao; Reflinur; Md. Lutfor Rahman; Yunjoo Lee; Jeonghwan Seo; Backki Kim; Hee-Jong Koh (Genes & Genomics, 2015)

QTLs for hybrid fertility and their association with female and male sterility in rice - Reflinur; Joong Hyoun Chin; Sun Mi Jang; Backki Kim; Joohyun Lee; Hee-Jong Koh (Genes & Genomics, 2012)

Mapping quantitative trait loci conferring blast resistance in upland indica rice (Oryza sativa L.) - Puji Lestari; Kurniawan Rudi Trijatmiko; Reflinur; Ahmad Warsun; Tasliah; Isabelita Ona; Casiana Vera Cruz; Masdiar Bustamam (Journal of Crop Science and Biotechnology, 2011)